Integrasi Pelatihan Kewirahusahaan Berbasis Digital untuk Pengembangan UMKM dan Peningkatan Ekonomi Lokal - Efendi, Nur Avan Raditya; Faisal, Ade (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Digital-based entrepreneurship training is a strategic innovation that plays an important role in developing the capacity of Micro, Small, and Medium Enterprises (MSMEs) by utilizing technology to expand access and increase the effectiveness of flexible and interactive learning. This approach not only improves individual skills in aspects of business management, digital marketing, and financial management, but also strengthens the local economic ecosystem through the development of synergistic business networks and sustainable business growth, thereby contributing to job creation and improving community welfare. The success of this training is highly dependent on the availability of technological infrastructure, facilitator competence, and collaboration between the government, private sector, and educational institutions, so that the development of an integrated and sustainable training model is key to facing the challenges of globalization and digital transformation in the modern era.